Does parents' perception of the environment associates with outdoor physical activity duration in low-income preschoolers? - Cleene Tavares de Souza; Glauber Carvalho Nobre; Anastácio Neco de Souza Filho; Roseanne Gomes Autran; Andréia Pizarro; Jorge Augusto Pinto da Silva Mota; Clarice Maria de Lucena Martins (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
Parents' perception of the environment may influence the time spent in outdoor physical activities in pre-school children. This study aimed to analyze the association between parents' perception of the environment and outdoor physical activities outside the school in low-income preschoolers. In total, 129 preschoolers aged 3 to 5 years (4.4 years ± 0.7 years, 50% boys) and their parents participated in the study. An adapted version of the Neighborhood Environmental Walkability Scale was used to obtain parents' environmental perceptions. Outdoor physical activities was measured based on two questions considering the usual time spent in these activities during week and weekend days. Information on sociodemographic was collected by interview. Logistic regression was used to analyze the associations. Statistical analyses were conducted using SPSS, version 21.0. Most preschoolers (76.9%) had ≤ 2 hours/day in outdoor physical activities during the week while at the weekend, 65.9% reached > 2 hours. Parents' perception of unsafe traffic (OR = 0.39; p = 0.03) was associated with higher chances for a shorter time in outdoor physical activities both during the week and at the weekend (OR = 0.46; p = 0.04). Moreover, preschoolers' whose parents perceive a lack of places to walk (OR = 0.33; p = 0.02) and unsafe night time (OR = 0.36; p = 0.04) are more likely to spend less time in outdoor physical activities during the week. After adjustments for sociodemographic confounders, the perception of unsafe traffic (OR = 0.26; p = 0.01) and places to walk (OR = 0.15; p = 0.01) were predictors of preschooler's shorter time in outdoor physical activities during the week. Parents' perception of unsafe traffic and places to walk were associated with less time in outdoor physical activities in low-income preschoolers.